Psychological Issues in Bangladeshi Children for Covid-19: Losing Interest in Education - R. Riteshkarmaker (Universitas Pendidikan Indonesia (UPI), 2023)
In Bangladesh, COVID-19 has had a significant impact on both the psyche and future of both children and adolescents. It destroys, the environment and the future of children. Children suffer more than adults during COVID-19 in a wide range of underdeveloped and impoverished nations, including Bangladesh. There has been an analysis of the effect of Covid-19 on children in Sherpur Sadar Upazilla, Sherpur, Bangladesh. In addition to dealing with psychological concerns, they were unable to study or eat adequately. This article used a quantitative technique to illustrate the situations in which kids struggled with school and their lack of interest in working for a degree for COVID-19. In the 14 months that the corona outbreak lasted, schools were shuttered. Despite the existence of numerous institutions, there were few educational opportunities. The students' propensity to study has suffered greatly as a result. Students who were placed under house arrest for an extended period experienced a variety of mental health issues. They are hesitant to continue their studies because of these problems.